Adherence to Recommended Cervical Cancer Screening Based on Human Papillomavirus Vaccination Status [17OP]. (May 2017) - Terk, Daniel; Bonham, Adrienne; Caveglia, Sarah; Li, Dongmei; Prast, Brendan; Day, Serena
Abstract : INTRODUCTION: Human Papillomavirus (HPV) vaccination and routine cervical cytology both aim to prevent cervical cancer, however limited data exists for how vaccination affects patient behavior. The objective of this study is to examine if adherence to cervical cancer screening is affected by HPV vaccination. METHODS: Retrospective chart review was completed using billing data for cervical cytology and HPV vaccination from 2006 to 2010. These years were chosen because the HPV vaccine was released in 2006, and annual cervical cytology was recommended until 2010. Participants were included based on birth year, ensuring participants were old enough to obtain cervical cancer screening and young enough to receive the HPV vaccine. For inclusion two or more cervical cytology samples were needed, and vaccination status confirmed via billing data or chart review. Adherence to cervical cancer screening was assessed using a ratio of appropriately timed pap smears to all pap smears in the study period. RESULTS: 2, 397 charts were reviewed, 943 were included, of these 350 were vaccinated and 593 were unvaccinated. Adherence to screening was not affected by overall vaccination status. For the sub-group of women vaccinated mid-study, adherence was compared before and after vaccination and it was found that these women were significantly less likely to be adherent after vaccination (N=140, adjusted OR 0.19, CI 0.08 - 0.49). CONCLUSION: Comparing patterns of adherence to cervical cancer screening before and after vaccination shows that women were less likely to adhere to screening guidelines after HPV vaccination. This may represent an unintended consequence of the HPV vaccination program.